3D electrical imaging of an archaeological site using electrical and electromagnetic methods - Osella, Ana Maria (2005)
Floridablanca is an 18th century archaeological site located in southern Argentina. Archaeological investigations at the site began in 1998, and in 2000 we started a project to perform geophysical studies there. In this paper, we report the implementation of electrical and electromagnetic (EM) methods in a sector of the site that corresponds to the settlers' houses. The objective of the project was to characterize the zone and the buried archaeological structures (adobe walls, tiles from a collapsed roof) with 2D and 3D electrical and EM techniques. We first applied an EM induction method covering a 600-m2 area with a frequency ranging from 1000 to 19 000 Hz. A 3D visualization of the in-phase and quadrature components gave an initial description of anomalies possibly associated with buried structures. We then performed dipole-dipole profiles and inverted the data to obtain the corresponding 2D and 3D electrical images. Finally, after correlating the information obtained from the analysis of both EM and electrical data, we performed a more localized 3D dipole-dipole mesh (25 m2) to achieve the final electrical image of the most representative buried structure. The combination of both techniques allowed us to map two entire houses and to identify three types of walls: main, separating, and inner. These results have been confirmed by an archaeological excavation. © 2005 Society of Exploration Geophysicists. All rights reserved.